2003
DOI: 10.1042/bj20021176
|View full text |Cite
|
Sign up to set email alerts
|

Upstream stimulatory factor activates the vasopressin promoter via multiple motifs, including a non-canonical E-box

Abstract: We have described previously a complex E-box enhancer (-147) of the vasopressin promoter in small-cell lung cancer (SCLC) extracts [Coulson, Fiskerstrand, Woll and Quinn, (1999) Biochem. J. 344, 961-970]. Upstream stimulatory factor (USF) heterodimers were one of the complexes binding to this site in vitro. We now report that USF overexpression in non-SCLC (NSCLC) cells can functionally activate vasopressin promoter-driven reporters that are otherwise inactive in this type of lung cancer cell. Site-directed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…Sequence analysis of the corresponding random DNA inserts revealed that only four of the 11 probes contained a perfect E-box sequence (CACGTG), and the remaining seven probes contained E-boxes with a single mismatch resulting in either the binding motif CACGTT or CACGGG. Both mismatched sequences represent so-called noncanonical E-box motifs that have been found to bind E-box-binding transcription factors in certain promoters (Harris et al 2000;Coulson et al 2003). Interestingly, the noncanonical E-box motif CAC GTT formed the strongest CLOCK/BMAL1 complex in the screen, and this motif has been reported by Yoo et al (2005) to be bound by CLOCK/BMAL1 in vivo and to drive the expression of the Per2 gene in transgenic mice.…”
Section: Identification Of Established Circadian Transcription Factormentioning
confidence: 99%
“…Sequence analysis of the corresponding random DNA inserts revealed that only four of the 11 probes contained a perfect E-box sequence (CACGTG), and the remaining seven probes contained E-boxes with a single mismatch resulting in either the binding motif CACGTT or CACGGG. Both mismatched sequences represent so-called noncanonical E-box motifs that have been found to bind E-box-binding transcription factors in certain promoters (Harris et al 2000;Coulson et al 2003). Interestingly, the noncanonical E-box motif CAC GTT formed the strongest CLOCK/BMAL1 complex in the screen, and this motif has been reported by Yoo et al (2005) to be bound by CLOCK/BMAL1 in vivo and to drive the expression of the Per2 gene in transgenic mice.…”
Section: Identification Of Established Circadian Transcription Factormentioning
confidence: 99%
“…In later experiments, including all of the siRNA experiments, the CA77 cells were transfected by LipofectAMINE 2000 (Invitrogen) as described previously (22). NCI-H460 cells were transfected by electroporation essentially as described (21). The conditions were 0.8 ml of cells (1 ϫ 10 7 cells/ml) in a 0.4-cm cuvette with 10 g of luciferase reporter DNA and 13 g of each expression vector DNA using a Bio-Rad Gene Pulser II at 260V, 1050 F. Immediately after electroporation, 0.4 ml of cells were pipetted into medium in a 10-cm dish and cultured for 20 -24 h prior to harvest.…”
Section: Methodsmentioning
confidence: 99%
“…This non-small cell lung cancer line was chosen because it expresses relatively low levels of USF-1 and -2 proteins, and overexpression of USF in this cell type has been shown previously to strongly activate the arginine vasopressin promoter (21). The need for a cell line with low USF levels was driven by our finding that overexpression of USF-1 and -2, with or without Foxa2, had little or no effect on enhancer activity in COS-7 cells (data not shown).…”
Section: Foxa2 and Usf Activation Of Ct/cgrpmentioning
confidence: 99%
“…uSF1 also mediates the transcription of many neuropeptides (33)(34)(35)(36), surfactant protein A in the lung (37), genes in lung tumors (38) which include hTERT as the immortalizing telomerase subunit (39,40) and CDK4 as the cell cycle regulator (41). uSF1 can also regulate neuropeptide genes in lung cancer, particularly arginine vasopressin (AVP) (42,43).…”
Section: Discussionmentioning
confidence: 99%